Efficacy of Oral Transmucosal Fentanyl Citrate for Premedication in Patients for Surgery under General Anesthesia - Singh, Raj Bahadur (Anesth Essays Res, 2017)
BACKGROUND: Oral transmucosal fentanyl citrate (OTFC), a water soluble salt when mixed in saliva is 80% nonionized; making it the only opioid suitable for transmucosal absorption. OTFC has rapid onset of action (3–5 min) with peak effect at 20–40 min and total duration of activity is 2–3 h. AIMS: This study aims to determine the efficacy of OTFC as premedicant in patients scheduled for surgery under general anesthesia (GA) and to assess the effects of OTFC on anxiety, sedation. SETTINGS AND DESIGN: A prospective randomized study. SUBJECTS AND METHODS: Patients between 21 and 60 years of age in American Society of Anesthesiologists physical status Classes I and II scheduled for elective surgery under GA were randomly assigned to three groups of 30 each: OTFC, placebo, and control. Mean arterial blood pressure (MAP), heart rate (HR), respiratory rate (RR), and oxygen saturation (SpO(2)) along with anxiety and sedation scores were recorded as baseline and upon entering the operation theater. Adverse effects were also recorded. STATISTICAL ANALYSIS USED: Statistical analysis was done using Statistical Package for Social Sciences Version 15.0 Statistical Analysis Software. RESULTS: No significant differences were found in MAP, HR, RR, or SpO(2) among the groups. OTFC group demonstrated significantly higher levels of anxiolysis than the control group (P < 0.05). No significant difference in sedation score was found. No remarkable adverse effects were observed. CONCLUSIONS: OTFC is an effective anxiolytic in adult with minimal risks and side effects. It is readily acceptable by the patients in its given form.